Grameen Bank Project “Social Business” Muhammad Yunus: Proyek Bank Grameen “Bisnis Sosial” Muhammad Yunus - Nurhayati, Nurhayati (Universitas Muhammadiyah Sidoarjo, 2016)
Social Entrepreneurship is known to be effective in overcoming the problem of poverty syndrome in various countries. Perspectives on the term social entrepreneurship is growing and diverse among scholars, practitioners, and related institutions. However, they agreed that the final goal to be achieved should lead to the interests and empowerment of society. Muhammad Yunus of Bangladesh has proved the power of social entrepreneurship through the development of the mindset that every human being has marketable skills, unlimited potential, including the entrepreneurial spirit. The poverty of the people is not due to laziness or lack of skills, but the opportunity and are less favorable policy factors on them. Finally, Yunus fulfilled his dream and history has recorded his success in tackling the problem of poverty through the micro-finance institution